2014
DOI: 10.1021/la501402q
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gene Expression Promoted by Hybrid Magnetic/Cationic Block Copolymer Micelles

Abstract: We report on novel gene delivery vector systems based on hybrid polymer-magnetic micelles. The hybrid micelles were prepared by codissolution of hydrophobically surface modified iron oxide and amphiphilic polystyrene-b-poly(quaternized 2-vinylpyridine) block copolymer (PS-b-P2QVP) in organic solvent. After extensive dialysis against water, micelles with positively charged hydrophilic corona of PQVP and hydrophobic PS core were prepared, in which magnetic nanoparticles were randomly distributed. The hybrid mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 40 publications
(59 reference statements)
3
18
0
Order By: Relevance
“…Hence, the two peaks can be assigned to unbound DNA and magnetopolyplexes. The results are in good agreement with agarose gel electrophoresis performed earlier showing presence of unbound DNA at those ratios.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, the two peaks can be assigned to unbound DNA and magnetopolyplexes. The results are in good agreement with agarose gel electrophoresis performed earlier showing presence of unbound DNA at those ratios.…”
Section: Resultssupporting
confidence: 91%
“…After extensive dialysis against water for 7 d, micelles with positively charged hydrophilic shell of PQVP and hydrophobic PS core loaded with magnetic nanoparticles were obtained. The detailed procedure is described elsewhere . The concentration of magnetic nanoparticles was 10% in respect to the PS block.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers of vinylpyridines may form complexes with the genetic material after quaternization of tertiary amine groups in their pyridine rings or protonation at pH values lower than 5. Polyelectrolyte complexes of quaternized poly(4‐vinylpyridine) (P4VP) or poly(2‐vinylpyridine) with genetic material, such as plasmid DNA, were already investigated and it was shown that this polymer may be used in gene therapy studies.…”
Section: Introductionmentioning
confidence: 99%
“…The micelles formed thereof have previously been used as gene delivery vector systems manifesting low cytotoxicity to eukaryotic cells and high cells internalization [16,17]. Block copolymers based on quaternized poly (2-vinylpyridine) (PQVP) and poly (2-(dimethylamino)ethyl methacrylate) (PDMAEMA) cationic moieties were used.…”
mentioning
confidence: 99%